Analisis Perbedaan Pendapatan Antara Petani Padi Sawah Sistem Pompanisasi dengan Petani Padi Sawah Sistem Tadah Hujan - Juli Astuti Daulay; Ahmad Rafiqi Tantawi; Gustami Harahap (Universitas Medan Area, 2021)
The purpose of this study was to analyze income differences between farmers pumping system with rainfed rice farm then analysis factor affecting the income of rice farmers in the pumping system with the system of rainfed rice farmers. The method that was used for farmers is purposive sampling. Data analysis method is used average on different test methods (compare means) by using independent sample t-test with two different irrigation systems, analyzed income, analyze profit and linear regression. The results showed that there were no significant income differences between income differences between farming pumping system with rainfed rice farm. In this study the factors that influencethe income of rice farmers in the pumping system in Pematang Johor Village Labuhan Deli District Deli Serdang District significantly affect the income of rice farmers are labor costs, is the costs of pesticides and the costs of fertilizer. And to factors that influence the income of rice farmers in the system of rainfed rice farmers in Pematang Johor Village Labuhan Deli District Deli Serdang District significantly affect the income of rice farmers are costs of fertilizer. While the non significant labor costs, and the costs of pesticides.